Evolution of the low-temperature Fermi surface of superconducting FeSe1−xSx across a nematic phase transition - Coldea, AI; Blake, SF; Kasahara, S; Haghighirad, AA; Watson, MD; Knafo, W; Choi, ES; McCollam, A; Reiss, P; Yamashita, T; Bruma, M; Speller, SC; et al. (Springer Nature, 2019)
The existence of a nematic phase transition in iron-chalcogenide superconductors poses an intriguing question about its impact on superconductivity. To understand the nature of this unique quantum phase transition, it is essential to study how the electronic structure changes across this transition at low temperatures. Here, we investigate the evolution of the Fermi surfaces and electronic interactions across the nematic phase transition of FeSe1−xSx using Shubnikov-de Haas oscillations in high magnetic fields up to 45 T in the low temperature regime down to 0.4 K. Most of the Fermi surfaces of FeSe1−xSx monotonically increase in size except for a prominent low frequency oscillation associated with a small, but highly mobile band, which disappears at the nematic phase boundary near x ~ 0.17, indicative of a topological Lifshitz transition. The quasiparticle masses are larger inside the nematic phase, indicative of a strongly correlated state, but they become suppressed outside it. The experimentally observed changes in the Fermi surface topology, together with the varying degree of electronic correlations, will change the balance of electronic interactions in the multi-band system FeSe1−xSx and promote different kz-dependent superconducting pairing channels inside and outside the nematic phase.